2018
DOI: 10.1021/acsnano.8b06692
|View full text |Cite
|
Sign up to set email alerts
|

Trap Passivation in Indium-Based Quantum Dots through Surface Fluorination: Mechanism and Applications

Abstract: Treatment of InP colloidal quantum dots (QDs) with hydrofluoric acid (HF) has been an effective method to improve their photoluminescence quantum yield (PLQY) without growing a shell. Previous work has shown that this can occur through the dissolution of the fluorinated phosphorus and subsequent passivation of indium on the reconstructed surface by excess ligands. In this article, we demonstrate that very significant luminescence enhancements occur at lower HF exposure though a different mechanism. At lower ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(261 citation statements)
references
References 73 publications
(126 reference statements)
12
242
2
1
Order By: Relevance
“…22 On the other hand, our result is not consistent with other reports that suggest that HF treatment removes electron traps on InP QDs by the passivation of surface indium dangling bonds. 22,23 Exciton dynamics in InP@ZnS core@shell QDs: passivation of both electron and hole traps…”
Section: MLcontrasting
confidence: 99%
See 1 more Smart Citation
“…22 On the other hand, our result is not consistent with other reports that suggest that HF treatment removes electron traps on InP QDs by the passivation of surface indium dangling bonds. 22,23 Exciton dynamics in InP@ZnS core@shell QDs: passivation of both electron and hole traps…”
Section: MLcontrasting
confidence: 99%
“…[20][21][22][23][24][25][26] The rst passivation method employed a post-synthetic HF treatment of InP QDs under illumination. [20][21][22][23]25 The HF treatment has been suggested to remove the surface P dangling bonds through a photochemical reaction of trapped holes with the P atom, which is then attacked by the F À ions and eventually detach from the InP surface. 25 Meanwhile, a recent study suggested an alternative/complementary mechanism where the F À treatment may act through removing the electron traps caused by the surface indium dangling bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This can create a situation where in the presence of Al oxide allows the electrons in the cores to be transferred to the ligands or causes partial leakage of electron wavefunctions. [ 39–41 ]…”
Section: Emission Dynamics Of Pbs and Cdse/zns Qdsmentioning
confidence: 99%
“…Квантовые точки бывают двух типов: коллоидные [299,300] и эпитаксиальные [301,302]. Для пассивации коллоидных квантовых точек InP и InAs, формируемых в растворах оксида триоктилфосфина, используется, как правило, травление растворами HF или NH 4 F [299,303,304]. Такая обработка приводит к фотохимическому удалению оборванных связей поверхностных атомов фосфора (мышьяка) и к последующей пассивации поверхностных атомов индия лигандами оксида триоктилфосфина [305].…”
Section: модификация характеристик полупроводниковых приборных структunclassified